Life course socioeconomic position and general and oral health in later life: Assessing the role of social causation and health selection pathways. (March 2022) - Letelier, Alejandra; Jivraj, Stephen; Heilmann, Anja; Watt, Richard G.; Tsakos, Georgios
Abstract: Objective: To examine the pathways between life course socioeconomic position (SEP) and general and oral health, assessing the role of two competing theories, social causation and health selection, on a representative sample of individuals aged 50 years and over in England. Methods: Secondary analysis from the English Longitudinal Study of Ageing Wave 3 data (n = 8659). Structural equation models estimated the social causation pathways from childhood SEP to adult self-rated general health and total tooth loss, and the health selection pathways from childhood health to adult SEP. Results: There were direct and indirect (primarily via education, but also adult SEP, and behavior) pathways from childhood SEP to both health outcomes in older adulthood. There was a direct pathway from childhood health to adult SEP, but no indirect pathway via education. The social causation path total effect estimate was three times larger for self-rated general health and four times larger for total tooth loss than the health selection path respective estimates. Conclusions: The relationship between SEP and health is bidirectional, but with a clearly stronger role for the social causation pathway. Highlights: Recognize the social determinants of healthy ageing is more relevant than ever. A life course approach was used to explore health and socioeconomic pathways. Structural equation models were used to test social causation and health selection. Childhood and adult socioeconomic position shape general and oral health at old age. There is a bidirectional relationship between life course circumstances and health.